Hardness, compressive strength and resilience of complete denture lining materials: an in situ study - Hugo de CARVALHO JUNIOR; Vítor Hugo Marçal de CARVALHO; Roberta Tarkany BASTING (Faculdade São Leopoldo Mandic, 2020)
ABSTRACT Objective The aim of this study was to evaluate the in situ hardness, compressive strength and resilience of soft lining materials used in total removable prostheses in different time intervals Methods total of 48 rectangular test specimens (10 x 3 x 2 mm) were fabricated of each of the polyvinylsiloxane-based soft liner (Mucopren Soft) and acrylic resin-based material (Trusoft), which were placed on total removable prostheses bases of 12 volunteers (n = 12). The hardness (Shore A), compressive strength (in MPa) and resilience (in Kgf/cm2) were evaluated in different time intervals: 0, 7, 30 and 60 days, at three different locations of the specimens surface. Results The two-way ANOVA and Tukey test showed that the polyvinylsiloxane-based soft liner presented higher hardness values (p = 0.0113) and higher compressive strength (p=0.0252) than the acrylic resin-based material at immediate and 7 days evaluations. The polyvinylsiloxane-based soft liner presented higher resilience values than the acrylic resin-based material at all times (p = 0.0133). Hardness and compressive strength were similar for both materials at 30 and 60 days evaluations. Conclusions For both materials,there was a tendency for an increase of hardness, compressive strength and resilience over time, influenced by the composition of the tissue conditioner. The polyvinylsiloxane-based soft liner presented higher hardness, compressive strength and resilience than the acrylic resin-based material, specially considering a long-term evaluation up to 60 days.